The effect of disease modifying therapies on brain atrophy in patients with relapsing-remitting multiple sclerosis: a systematic review and meta-analysis - Tsivgoulis, Georgios; Katsanos, Aristeidis H; Grigoriadis, Nikolaos; Hadjigeorgiou, Georgios M; Heliopoulos, Ioannis; Kilidireas, Constantinos; Voumvourakis, Konstantinos (PloS one, 2015)
BACKGROUND: The aim of the present meta-analysis was to evaluate the effect of disease-modifying drugs (DMD) on brain atrophy in patients with relapsing-remitting multiple sclerosis (RRMS) using available randomized-controlled trial (RCT) data. METHODS: We conducted a systematic review and meta-analysis according to PRISMA guidelines of all available RCTs of patients with RRMS that reported data on brain volume measurements during the study period. RESULTS: We identified 4 eligible studies, including a total of 1819 RRMS patients (71% women, mean age 36.5 years, mean baseline EDSS-score: 2.4). The mean percentage change in brain volume was found to be significantly lower in DMD versus placebo subgroup (standardized mean difference: -0.19; 95%CI: -0.27--0.11; p<0.001). We detected no evidence of heterogeneity between estimates (I2 = 30%, p = 0.19) nor publication bias in the Funnel plots. Sensitivity analyses stratifying studies according to brain atrophy neuroimaging protocol disclosed no evidence of heterogeneity (p = 0.16). In meta-regression analyses, the percentage change in brain volume was found to be inversely related with duration of observation period in both DMD (meta-regression slope = -0.03; 95% CI: -0.04--0.02; p<0.001) and placebo subgroups (meta-regression slope = -0.05; 95% CI: -0.06--0.04; p<0.001). However, the rate of percentage brain volume loss over time was greater in placebo than in DMD subgroup (p = 0.017, ANCOVA). CONCLUSIONS: DMD appear to be effective in attenuating brain atrophy in comparison to placebo and their benefit in delaying the rate of brain volume loss increases linearly with longer treatment duration.
Keywords: výsledek terapie; mozek; Treatment Outcome; randomizované kontrolované studie jako téma; Randomized Controlled Trials as Topic; Atrophy; neuroprotektivní látky; relabující-remitující roztroušená skleróza; lidé; Neuroprotective Agents; Multiple Sclerosis, Relapsing-Remitting; Brain; Humans; atrofie